Synthesis of Cu\(^+\)/bipyridyl Based Complex Towards Dye Sensitized Solar Cell Application - Son, Vuong; Ha, Nguyen Ngoc; Thuy, Luong Thi Thu; Thinh, Tran Quang; Tuan, Mai Anh (Communications in Physics, 2016)
This study aims to synthesize the Cu+/bipyridyl-based complex using Sonogashira cross coupling. The structure of the ligand and the complex were investigated by nuclear magnetic resonance spectroscopy; by single crystal X-ray diffraction and by UV-VIS absorption spectroscopy. The obtained experimental results were in good agreement with the theoretical calculations. The complex is a potential candidate to be the photo sensitizer in dye-sensitized solar cells.